KONSEP PENGELOLAAN SATUAN PENDIDIKAN BERDASARKAN KURIKULUM MERDEKA DI TK YAYASAN ISLAM TASIKMALAYA - Sansofa, Clevarisza Aulia; Auliya, Sinta; Danesta, Nasywaa Adzani Fitria; Sianturi, Risbon (Pendidikan Guru PAUD, FKIP, Univ Muhammadiyah Tasikmalaya, 2025)
Teachers and parents have an important role in education, especially ensuring quality education for the nation’s children, therefore it is necessary to implement and manage a curriculum that suits the needs and development of children. This research was conducted at Yayasan Islam Tasikmalaya Kindergarten, which is one of the early childhood education institutions in Tasikmalaya. The method used in this research is descriptive qualitative method and literature review. Descriptive qualitative research is a research method that tends to be descriptive and uses analysis. Data collection techniques used by researchers in this study are observation, interview, and documentation techniques. This research involved a resource person who is the principal of the Tasikmalaya Islamic Foundation Kindergarten. Based on the results of the research, in the management of the education unit at the Tasikmalaya Islamic Foundation Kindergarten, the principal implements a School-Based Management (MBS) policy. In addition, the Tasikmalaya Islamic Foundation Kindergarten has used the latest curriculum according to national education policy, namely the use of the Merdeka Curriculum.